Y - y₁ = m(x - x₁)
y - 3 = 4(22 - 2)
y - 3 = 4(20)
y - 3 = 80
+ 3 + 3
y = 83
The answer is 5.477225575.... or 5.5 if you want the simplified ansewer
Answer:
x = -5
Step-by-step explanation:
Simplifying
6x + -3(x + -8) = 9
Reorder the terms:
6x + -3(-8 + x) = 9
6x + (-8 * -3 + x * -3) = 9
6x + (24 + -3x) = 9
Reorder the terms:
24 + 6x + -3x = 9
Combine like terms: 6x + -3x = 3x
24 + 3x = 9
Solving
24 + 3x = 9
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-24' to each side of the equation.
24 + -24 + 3x = 9 + -24
Combine like terms: 24 + -24 = 0
0 + 3x = 9 + -24
3x = 9 + -24
Combine like terms: 9 + -24 = -15
3x = -15
Divide each side by '3'.
x = -5
Hope this Helps
I hope this is correct
Answer: 168
Step-by-step explanation: 70/5=14. 14x7=98. 70+98=168.